Delayed Payment Contracts and a Firm's Propensity to Hire Older Workers - Hutchens, Robert (Journal of Labor Economics, 1986)
There are jobs for which firms employ older workers but tend not to hire new older workers. This may be attributable in part to implicit contracts that discourage worker shirking and malfeasance by shifting compensation to the end of the contract. Such "delayed payment" contracts can introduce a form of fixed costs into the employment relationship. Much as with hiring and training costs, these fixed costs lead firms to hire primarily young (long-term) workers. While firms employ older workers-workers who are serving out the last years of their contract-they tend not to hire them. This paper presents empirical evidence that is consistent with this argument.